Impact of workplace ostracism on knowledge hoarding: Mediating role of defensive silence and moderating role of experiential avoidance - Bilal Khalid; Rimsha Iqbal; Syed Danial Hashmi (Future Business Journal, 2020)
The purpose of this study is to investigate the underlying mechanism through which knowledge hoarding is triggered among ostracized employees at workplace. Drawing on conservation of resource theory, the study investigates the mediating role of defensive silence in this relationship. Further, the study also examines the moderating role of experiential avoidance between workplace ostracism and defensive silence. Using multi-layered and convenient sampling technique, data were collected from 225 employees working in the hospitality industry in Pakistan. The results revealed that workplace ostracism significantly influences employees' knowledge hoarding behavior both directly and through defensive silence. Furthermore, contrary to the expectation, the combined effect of workplace ostracism and experiential avoidance on defensive silence was found insignificant, which we have discussed. The study provides insights for managers to break the knowledge hoarding cycle and create new models for interaction and knowledge sharing among employees at workplace.
Keywords: 650; Defensive silence; Experiential avoidance; Knowledge hoarding; Workplace ostracism